Perfil epidemiológico da morte materna no estado do pará no período de 2007 a 2011 - FERREIRA, Jadson João Ferreira (2019)
Maternal mortality is defined as death of a woman during pregnancy or up to 42 days after the end of this, and is an important indicator of health because its occurrence reflects the quality of health care of women in a given population, provides information on the performance of health services and the inequities that exist between different socioeconomic strata. In this perspective the work showed the epidemiological profile of maternal death in women of reproductive age in the state of Pará in the period 2007-2011. This is a descriptive study, a quantitative crosssectional and retrospective. The study was conducted using data provided by the Mortality Information System of the Department of Public Health State of Pará, SESPA. For data analysis we used the simple and relative frequencies of categorical variables (total number of deaths, age, color, education and cause of death) and calculations of the Maternal Mortality Ratio of gross. The description of the variables given in numbers and percentages expressed in the form of tables and charts. The results revealed that the maternal mortality ratio were higher in the years 2011 (60.57) and 2007 (58.60), deaths predominated aged 20-29 years (44.63%), in skinned women (76.83%) and 4-7 years of education (35.85%), the main causes were hypertension, hemorrhagic syndromes and infection with the respective percentage of the total number of deaths (31.95%), (11.46%) and (7.80%). We conclude that reducing maternal mortality, in addition to political will, requires the training of health professionals, for early diagnosis of the vulnerability of pregnant and operating measures to avoid the occurrence of maternal death.